2014
DOI: 10.1073/pnas.1308418111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of plexin signaling in vivo

Abstract: Mammalian plexins constitute a family of transmembrane receptors for semaphorins and represent critical regulators of various processes during development of the nervous, cardiovascular, skeletal, and renal system. In vitro studies have shown that plexins exert their effects via an intracellular R-Ras/M-Ras GTPase-activating protein (GAP) domain or by activation of RhoA through interaction with Rho guanine nucleotide exchange factor proteins. However, which of these signaling pathways are relevant for plexin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 59 publications
2
86
0
Order By: Relevance
“…However, recent biochemical and structural studies demonstrated that the recombinant GAP domain of plexins promoted GTP hydrolysis of recombinant Rap1 but not R-Ras (20). A functional GAP domain and GAP activity were required for proper early embryogenesis in BAC transgenic mice that expressed plexin B1 and D1 (21). In this study, we demonstrated sema3e-mediated inhibition of Rap1 activation and LFA-1-dependent adhesion directly through the Rap1 GAP activity of plexin D1.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, recent biochemical and structural studies demonstrated that the recombinant GAP domain of plexins promoted GTP hydrolysis of recombinant Rap1 but not R-Ras (20). A functional GAP domain and GAP activity were required for proper early embryogenesis in BAC transgenic mice that expressed plexin B1 and D1 (21). In this study, we demonstrated sema3e-mediated inhibition of Rap1 activation and LFA-1-dependent adhesion directly through the Rap1 GAP activity of plexin D1.…”
Section: Discussionmentioning
confidence: 53%
“…A recent in vitro biochemical study demonstrated the selective GAP activity of plexin D1 for Rap1 rather than for R-Ras/M-Ras (20). Interestingly, the GAP activity of plexin D1 functioned independently of R-Ras and M-Ras activity during cardiovascular development and skeletal morphogenesis throughout embryogenesis (21). Sema3e/plexin D1 was also reported to be important for thymocyte positioning via regulation of b 1 integrin activation (22)(23)(24).…”
mentioning
confidence: 99%
“…Functionally, sinusoidal dilatation and enhanced angiogenesis as seen in endothelial Notch signaling-deficient LSECs may promote hepatic metastasis (38). Notably, sinusoidal dilatation is a common end point of several signaling defects in LSECs; for example, plexin B2-transgenic mice defective in Rho guanine nucleotide exchange factor binding show sinusoidal dilatation and further abnormalities in the architecture of the liver vasculature (39). Recently, LXRα has This GATA4-dependent transcriptional program determines the functional competence of the hepatic sinusoidal endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] In the cases of plexin-D1 and plexin-B1 it was demonstrated that most of the developmental effects of these plexins are lost if the function of this GAP domain is compromised. 28 Type-A plexins associate spontaneously to form homodimers 11,12 or heterodimers. 29 Recent data indicates that activation of plexin signaling by semaphorins that bind directly to plexins such as sema6A is likely to be associated with a change in the spatial organization of plexin dimers, shifting the conformation from the inactive to the active form.…”
Section: Plexinsmentioning
confidence: 99%